Ketamine and depression: a narrative review - Corriger A; Pickering G (Dove Medical Press, 2019)
Alexandrine Corriger,1,2 Gisèle Pickering1,21Neuro-Dol Laboratory Inserm 1107, Clermont Auvergne University, Clermont-Ferrand, France; 2Clinical Pharmacology Department CPC/CIC Inserm 1405, Clermont-Ferrand University Hospital, Clermont–Ferrand, FranceCorrespondence: Gisèle Pickering Clinical Pharmacology Department CPC/CIC Inserm 1405, Clermont-Ferrand University Hospital, Bâtiment 3C, 58 Rue Montalembert, Clermont-Ferrand Cedex 1 F-63003, FranceTel +33 4 7 317 8416Fax +334 7 317 8412Email gisele.pickering@uca.frAbstract: Depression is the third leading cause of disability in the world. Depressive symptoms may be reduced within several weeks after the start of conventional antidepressants, but treatment resistance concerns one-third of patients who fail to achieve recovery. Over the last 20 years, ketamine, an antagonist of the N-methyl-D-aspartate receptor, has been described to have antidepressant properties. A literature review was conducted through an exhaustive electronic search. It was restricted to Cochrane reviews, meta-analyses, and randomized controlled trials (RCTs) of ketamine for major depressive disorder and/or bipolar disorder. This review included two Cochrane reviews, 14 meta-analyses and 15 trials. Ketamine was studied versus placebo, versus other comparators and as an anesthetic adjuvant before electroconvulsive therapy. In 14 publications, ketamine provided a rapid antidepressant effect with a maximum efficacy reached at 24 hrs. Its effect lasted for 1–2 weeks after infusion, but a longer-term effect is little reported. Ketamine does not seem to improve depressive symptoms at the end of electroconvulsive sessions. Safety and tolerability profiles with ketamine at low single dose are generally good in depressed patients. However, there is a lack of data concerning ketamine with repeated administration at higher doses. The clinical use of ketamine is increasing. Intranasal (S)-ketamine has recently been approved for depression by the Food and Drug Administration. It could be a promising treatment in depressed patients with suicidal ideation. Collectively, the level of proof of efficacy remains low and more RCTs are needed to explore efficacy and safety issues of ketamine in depression.Keywords: ketamine, depression, major depressive disorder, bipolar depression, suicide, efficacy